PENGARUH APE STEMPEL GEOMETRI TERHADAP KEMAMPUAN MENGENAL BENTUK-BENTUK GEOMETRI ANAK KELOMPOK B DI TK AINUN KIDS KECAMATAN TAMBANG KABUPATEN KAMPAR - Hussurur, Miftah; Chairilsyah, Daviq; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Based on the results of field observations on the ability to recognize the shape of the geometry of students has not developed optimally. So it is necessary to apply the stamp geometry. The purpose of this study was to examine the effect of stamp geometry educational game on the ability to recognize geometric shapes of children group B. This research was conducted at TK Ainun Kids Tambang District of Kampar District during February-March 2021. The research used experimental method with one group pre-test post-test design with 18 samples. The data collection technique used in this research is using observation sheet the ability to recognize the shape of the geometry. Data anlisis technique using t-test by using SPSS program ver 20. From result of data analysis obtained tcount equal to 30,433 bigger than t table = 2,110 with sig 0.000 <0.05. It can be concluded that there are differences in the ability to recognize shapes significant geometry before and after the use of stamp geometry educational game. Based on the results of the hypothesis test obtained that there is an effect of stamp geometry educational game on the ability to recognize geometric shapes for children group B at TK Ainun Kids Tambang District of Kampar District by 71.09%.Key Words: Geometric Shape, Stamp Geometry.